Therapeutic Potential of Silver Nanoparticles (AgNPs) as an Antimycobacterial Agent: A Comprehensive Review - Nilakshi Barua; Alak Kumar Buragohain (Antibiotics)
The uncontrolled emergence of multidrug-resistant mycobacterial strains presents as the primary determinant of the present crisis in antimycobacterial therapeutics and underscores tuberculosis (TB) as a daunting global health concern. There is an urgent requirement for drug development for the treatment of TB. Numerous novel molecules are presently undergoing clinical investigation as part of TB drug development. However, the complex cell wall and the lifecycle of M. tuberculosis within the host pose a significant challenge to the development of new drugs and, therefore, led to a shift in research focus towards alternative antibacterial compounds, notably nanotechnology. A novel approach to TB therapy utilizing silver nanoparticles (AgNPs) holds the potential to address the medical limitations imposed by drug resistance commonly associated with currently available antibiotics. Their broad-spectrum antimicrobial activity presents the utilization of AgNPs as a promising avenue for the development of therapeutics targeting mycobacterial-induced diseases, which can effectively target Mycobacterium tuberculosis, including drug-resistant strains. AgNPs can enhance the effectiveness of traditional antibiotics, potentially leading to better treatment outcomes and a shorter duration of therapy. However, the successful implementation of this complementary strategy is contingent upon addressing several pivotal therapeutic challenges, including suboptimal delivery, variability in intra-macrophagic antimycobacterial effect, and potential toxicity. Future perspectives may involve developing targeted delivery systems that maximize therapeutic effects and minimize side effects, as well as exploring combinations with existing TB medications to enhance treatment outcomes. We have attempted to provide a comprehensive overview of the antimycobacterial activity of AgNPs, and critically analyze the advantages and limitations of employing silver nanoparticles in the treatment of TB.